Search for the supersymmetric partner of the top quark in dilepton events from p(p)over-bar collisions at root s=1.8 TeV - Acosta, D; Affolder, T; Akimoto, H; Albrow, MG; Ambrose, D; Amidei, D; Anikeev, K; Antos, J; Apollinari, G; Arisawa, T; Artikov, A; Asakawa, T; et al. (2003)
The article discussed about the supersymmetric particles of the top quark in Dilepton events. The Collider Detector at Fermilab was used to gather supersymmetry particles. Due to the high mass, stop decays into the top quark were found kinematically inaccessible. The choice of the renormalization and factorization scale was considered as the source of uncertainty on the number of expected stop events.